Bile acid binding resin improves hepatic insulin sensitivity by reducing cholesterol but not triglyceride levels in the liver. Issue 1 (July 2015) - Tagawa, Hirotsune; Irie, Junichiro; Itoh, Arata; Kusumoto, Yukie; Kato, Mari; Kobayashi, Nana; Tanaka, Kumiko; Morinaga, Rieko; Fujita, Masataka; Nakajima, Yuya; Morimoto, Kohkichi; Sugizaki, Taichi; et al.
Highlights Bile acid binding resin improved hepatic insulin sensitivity by reducing cholesterol but not triglyceride in the liver. Fatty liver shionogi mice developed hepatic fat accumulation without dietary intervention. Bile acid binding resin improved glycemic controls in the patients with type 2 diabetes without reducing fat mass.